Factors affecting employee absenteeism in Nepalese commercial banks (Management Dynamics, 2020)
The impact of absenteeism on firms or even a nation’s economy is enormous, taking account of the costs associated with it. The major objective of the study is to analyze the relationship between job satisfaction, health status, family responsibilities, working condition, employee relation, occupational stress, and transportation problem and employee absenteeism of Nepalese commercial banks and to make suggestions to minimize the level of absenteeism of employees. However the specific objectives of this study are to analyze the perception of employees towards the absenteeism in Nepalese commercial banks, to determine factor affecting employee absenteeism in Nepalese commercial banks, to identify the reasons for absenteeism among employees in Nepalese commercial banks, to examine the relationship between job satisfaction, health status, family responsibilities, working condition, employee relation, occupational stress, transportation problem employee absenteeism in Nepalese commercial banks, to investigate the impact of job satisfaction, health status, family responsibilities, working condition, employee relation, occupational stress, transportation problem on employee absenteeism, to analyze the most important variable affecting employee absenteeism. The study found that job satisfaction is inversely related to absenteeism. The absent from a work situation that is sampling errors, scale inadequacies and the use of different measurement instruments. The psychological model that discusses this is the withdrawal model, which assumes that absenteeism represents individual withdrawal from dissatisfying working conditions. The study support in a negative association between absence and job satisfaction, especially satisfaction with the work itself. Medical-based understanding of absenteeism find support in research that links absenteeism with smoking, problem drinking, low back pain, and migraines Absence ascribed to medical causes is often still, at least in part, voluntary.